The Effectiveness of Honey For Swallowing Training in Stroke Patients With Dysphagia - Untari, Dyah; Putri, Nadia Oktiffany (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Stroke is the third leading cause of death in the world. Most individuals with stroke generally experience dysphagia. Food modification is one of the efforts to manage dysphagia. The aim of this study was to determine the effectiveness of honey for swallowing training in stroke patients with dysphagia. This study was a quantitative study with a quasi-experimental method. In this study, respondents were divided into two groups which were the intervention group and the control group. Each group consists of 11 respondents. After 3 days intervention, the results showed that a p-value (0.147) > 0.05, means that there was no significant difference between the two groups. However, the mean value of the honey as dysphagia management showed a higher value that the value of pudding. In conclusion, the findings highlight that honey is effective to be used as as a media for swallowing training in stroke patients with dysphagia.